Development Of E-Learning-Based Learning Media At Graha Nusantara University - Alwendi Alwendi; Erwina Azizah Hasibuan; Andi Saputra Mandopa; Tufan Adiguzel (Journal Neosantara Hybrid Learning, 2023)
The rapid development of information technology in the age of globalization has enabled the development of better information services in education. One of the new innovations in the use of educational media and technology-based learning resources and information is e-learning. The term e-learning has a very broad meaning and many experts explain the definition of e-learning from different angles. E-learning, or electronic learning, is learning that uses electronic devices as learning media and the Internet for learning activities. The concept of e-learning has influenced the process of transforming traditional education into digital form, both in terms of content and system. In addition, internet media enables real-time or non-real-time interaction between teachers and students. In the current era of communication technology has experienced rapid development, the internet is one of the technologies that is currently developing very rapidly. The internet seems to have become a basic human need from the top to the bottom, from the elderly to the children, even the internet has also gone global so that this world feels without boundaries. We can get information and communication in an instant, even from parts of the world that are very far from where we are.